Construction Cadres Party: Its Founding and Role in Iranian Political Life Until 2017 (Journal of the College of Basic Education, 2026)
After 1989, Islamic Iran witnessed the emergence of movements and parties operating under the regime of the Islamic Republic, sometimes different with official trends, but agreeing on the form of the system and the supreme guide, among them (Building Cadres Party), founded in 1996 at the end of the second session of the presidency of Mr. Ali Akbar Hashmi Rafsanjani, who was the main supporter of the party, participated in the parliamentary elections for several sessions of the Islamic Shura Council, secured several seats and played a role in the governments of Mohammad Khatami 1997-2005 and Hassan Rouhani 2013-2017) During the first period of his presidency, some party leaders received several ministries, and some party leaders were arrested during Ahmad Najadi's government.